Going underground: An exploration of the interfaces between underground urban transport infrastructure and its environment. (November 2018) - Darroch, Nathan; Beecroft, Mark; Nelson, John D.
Highlights: Urban underground metros have direct and indirect interfaces with their environment. Urban underground metros influence the design of their urban environment. The environment of urban underground metros influences their safe presence and operation. Comprehension of presence; property; protection, are essential to urban management. Abstract: With the continued urbanization and densification of cities worldwide the planning, and use of urban underground space (UUS) is of clear interest to urban and transport planners; and asset owners/managers. Effective strategies for the management of UUS and its environment once built are required and critical insight of how current use of these spaces affect and are affected by each other, enables effective planning and asset management strategies to be developed now and for the future. This paper argues that the management of existing and development of new urban infrastructure and its interfaces with UUS requires consideration of what is/will be there; who does/will own it; and how it must/will be protected. However, there appears to be a gap in the literature relating to how and why these interfaces occur and how they could and should be managed effectively. Taking the case of existing urban underground metro infrastructure, this paper demonstrates how understanding the presence, property, and protection interfaces of urban underground infrastructure and its environment at different levels of consideration is essential to urban and transport planning and management. The paper concludes with a challenge to current strategies and proposals for the development and management of UUS and its environment, questioning whether they are fit for current and future demands and changes.